Classification pattern and step-by-step procedure for cartilage grafts with silicone implants for nasal tip plasty in Asians. Issue 11 (November 2019) - Hwang, Ji; Kang, SY
Summary: Dorsal augmentation using silicone and tip plasty with autogenous cartilage is commonly performed in Asians. No study has investigated the classification pattern and step-by-step procedure for tip plasty using silicone implants. Therefore, this study classified cartilage grafts using silicone implants in Asians and developed a step-by-step procedure for their implementation. The study included 39 patients who had undergone augmentation rhinoplasty with a silicone implant combined with a conchal cartilage graft as a shield, an onlay graft, or both. We classified the implant-conchal cartilage complex into two main types (edge and no-edge types). In the edge type, the shield graft tip was located 1–2 mm above the silicone implant or onlay graft. In the no-edge type, it was located at the same level as the silicone implant or onlay graft. Each type was classified into three groups depending on the number of onlay grafts: group I, 0; group II, 1; and group III, ≥2. The cartilage complex was placed on the dorsum. The conchal cartilages were harvested through a post-auricular incision while preserving the radix helicis as cartilage bars. The donor site was closed primarily without a tie-over dressing. Of the 39 patients, 35 were satisfied with the outcome. Three revision operations for implant displacement and one revision for a patient who changed her dorsal height preference were performed. No donor site morbidity occurred. This method may be safe and reliable, with minimal morbidity associated with graft harvesting for tip plasty in Asians.